Evolution of Alcogel Physical Properties During the Aging Process. - Sherman, Matthew. (2017)
Abstract: The effects of aging alcogel on the thermophysical properties of the resulting aerogel are well understood. However, little has been done to characterize alcogel physical properties during the aging process. Previous work has shown that the porous structure undergoes physical changes as a result of aging, suggesting physical property change. A better understanding of the overall aging process can be developed by measuring the changes of the physical properties in the alcogel as a function of aging time and temperature. This work focuses on volume shrinkage and mechanical strength at different aging conditions. Volume shrinkage is determined by measuring sample dimensions before and after aging. Tests run at aging temperatures of 50 °C, 60 °C, 65 °C, and 70 °C have shown a maximum volume percent change occurring at different times. The maximum amount of shrinkage was found to be 2.5% at aging temperatures greater than 60 °C with aging time to fully cure becoming shorter at higher temperatures. The Avrami function was used to fit the data and showed an activation energy of 238.6 kJ/mol at high aging temperatures. In a parallel effort, tensile testing showed that the Young's modulus reaches an early peak over the same temperature interval and then levels out at a constant value of about 15 MPa as aging progressed. Both shrinkage and modulus leveled out at the same aging time, which was determined to be a function of the aging temperature.; Thesis (M.S.)--Tufts University, 2011.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Douglas Matson.; Committee: Luisa Chiesa, and Mez Polad.; Keywords: Mechanical Engineering, and Materials Science.